Higher chronic stress is associated with a decrease in temporal sensitivity but not in subjective duration in healthy young men - Yao, Zhuxi; Wu, Jianhui; Zhou, Bin; Zhang, Kan; Zhang, Liang (Frontiers in Psychology, 2015)
Maintaining accurate and precise temporal perception under conditions of stress is important. Studies in animal models and clinic patients have suggested that time perception can change under chronic stress. Little is known, however, about the relationship between chronic stress and time perception in healthy individuals. Here, a sample of 62 healthy young men completed Cohen’s Perceived Stress Scale (PSS) as a measure of chronic stress levels, while time perception was measured using a temporal bisection task. This task used short (400 ms) and long (1600 ms) visual signals as anchor durations. Participants were presented with a range of intermediate probe durations and were required to judge whether the durations were more similar to the short or the long anchor. Results showed that chronic stress was negatively related to temporal sensitivity indexed by the Weber ratio. However, there was no significant correlation between chronic stress and subjective duration indexed by the bisection point. These results demonstrate that higher chronic stress is associated with lower temporal sensitivity and thus provide evidence for a link between chronic stress and time perception in healthy adults.